Rules of engagement and the international law of military operations - Boddens Hosang, J. F. R. (Oxford monographs in international humanitarian and criminal law., 2020)
The book systematically analyses the relationship and interaction between rules of engagement (ROE) and the legal framework regulating armed conflicts, both at the international and national levels. At the international level, the relationship between ROE and human rights law and international humanitarian law is explored. At the national level, the book relates ROE to (comparative) criminal law. A separate chapter analyses the complex relationship between self-defence law and rules of engagement. 0It is the first monograph to comprehensively examine these issues and to analyse how ROE interact with the various sources of the (international) law of military operations, both in terms of the law as a source for these rules and how the law is reflected and implemented through them. In doing so, and based on the author's own experience, the book provides examples of how complicated, often controversial issues of law can be resolved while keeping the rules understandable at all levels of military operations. 0Aimed at both scholars and practitioners, the book provides a bridge between the academic world and the operational world. It provides new insights for both of those audiences in terms of understanding how the law applies to - and through - the rules on the use of force for military operations.